A systematic review of knowledge sharing behaviour in Chinese virtual communities: Multilevel influencing factors - Guangze Yang; Lay, Yoon Fah (Human Resource Management Academic Research Society (HRMARS), 2025)
This study systematically reviews knowledge sharing behaviors in Chinese virtual communities, focusing on multi-level influencing factors and research contributions of Chinese scholars. Using a systematic literature review approach and following the PRISMA framework, this study analyzes 65 high-quality articles published between 2000 and 2023, which are selected from a comprehensive dataset of 1,515 records retrieved from the CNKI database and the CNKI Academic Database. These complementary data sources provide a balanced view of Chinese research disseminated domestically and internationally. The results show that influencing factors cover individual, team, and organizational levels. Individuallevel factors, such as self-efficacy, perceived usefulness, and altruism, are mainly positive, while perceived costs and neuroticism represent a minority of negative influences. Team-level factors, including trust and social network centrality, and organizational-level factors, such as rewards and cultural norms, further enhance knowledge sharing behaviors. Despite much attention paid to positive drivers, negative effects such as information overload and privacy concerns remain underexplored. In addition, emerging technologies with transformative potential, such as blockchain and artificial intelligence, have received little attention.This review highlights the interdisciplinary and evolving nature of research on knowledge sharing behavior in Chinese virtual communities. It explores research gaps, including the need to study negative factors and emerging technologies, laying the foundation for future theoretical and practical advances.